PERKEMBANGAN ISLAM DI INDONESIA (Suatu Diskursus Tentang Awal Mula Islam Ke Nusantara) - Safri Gunawan (Institut agama islam negeri Padangsidimpuan, 2018)
Speaking of historical issues, it means that there is no final word because history writing is always open for rewriting because of the discovery of new data, theories, or methodologies which then open up opportunities for reinterpretation (new interpretations) to give rise to different perspectives, including the initial theme Islam entering the archipelago will always be interesting to discuss. Studying the beginning of Islam into Indonesia historically, means studying the journey of a past event about Islam in Indonesia (Islam in Indonesia) processually, which in this paper needs to be emphasized are five theories about the origin of Islam to the archipelago, namely Gujarat, Persian theory , Mecca, China, and Bangladesh to describe the roots or the beginning of the growth of Islamic teachings in Indonesia.